2018
DOI: 10.1016/j.asjsur.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of diclofenac sodium and paracetamol on colonic anastomosis: An experimental rodent model

Abstract: Bursting pressure, hydroxyproline levels, and fibrosis levels indicate that the perioperative use of paracetamol for analgesia when undergoing colonic anastomosis is safer than diclofenac sodium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
4
3
0
Order By: Relevance
“…These results were in accordance with the previous study that found metamizole tends to increase the incidence of anastomotic leakage [10]. In contrast, there was no significant inhibition in the anastomosis process of rat colon in the paracetamol group, which was supported by previous reports [11,12].…”
Section: Discussionsupporting
confidence: 93%
“…These results were in accordance with the previous study that found metamizole tends to increase the incidence of anastomotic leakage [10]. In contrast, there was no significant inhibition in the anastomosis process of rat colon in the paracetamol group, which was supported by previous reports [11,12].…”
Section: Discussionsupporting
confidence: 93%
“…These results were in accordance with previous study that found metamizole tends to increase the incidence of anastomotic leakage [9]. In contrast, there was no significant inhibition in the anastomosis process of rat colon in the paracetamol group, which was supported by previous reports [10,11].…”
Section: Discussionsupporting
confidence: 93%
“…These results were in accordance with the previous study that found metamizole tends to increase the incidence of anastomotic leakage [10]. In contrast, there was no significant inhibition in the anastomosis process of rat colon in the paracetamol group, which was supported by previous reports [11,12].…”
Section: Discussionsupporting
confidence: 93%